2018
DOI: 10.1002/solr.201800256
|View full text |Cite
|
Sign up to set email alerts
|

Energy Level Tuning of PEDOT:PSS for High Performance Tin‐Lead Mixed Perovskite Solar Cells

Abstract: Small bandgap Sn‐Pb mixed perovskite is generally regarded as the most promising structure to further enhance the power conversion efficiency of perovskite solar cells. However, the open circuit voltages (VOCs) are usually lower than expected. In this work, by doping the generally used hole transporting layer (HTL) poly(3,4‐ethylenedioxythiophene)‐poly(styrenesulfonate) (PEDOT:PSS) with a perfluorinated ionomer (PFI), we can tune the work function of it from −5.02 to −5.19 eV. This reduces the energy level mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 39 publications
1
53
0
Order By: Relevance
“…These results indicate that the solvent processing has different structuring mechanisms depending on the solvent nature. This finding is crucial for modifying the PEDOT:PSS film's properties for various applications, like transparent hole transport layer in the field of solar cells, [ 32–34 ] neuromorphic functional materials, [ 35,36 ] and bio‐sensing. [ 37,38 ]…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the solvent processing has different structuring mechanisms depending on the solvent nature. This finding is crucial for modifying the PEDOT:PSS film's properties for various applications, like transparent hole transport layer in the field of solar cells, [ 32–34 ] neuromorphic functional materials, [ 35,36 ] and bio‐sensing. [ 37,38 ]…”
Section: Resultsmentioning
confidence: 99%
“…Ning and co‐workers reported that using a perfluorinated ionomer (PFI) to modulate the PEDOT:PSS layer could tune the work function of HTL from −5.02 to −5.19 eV, thus bringing a smaller band mismatching at the perovskite/HTL interface. The PFI modified PSC has a PCE of 15.85%, featuring a V OC of 0.783 V which is about 50 mV higher than that of the reference device …”
Section: The Status Of Mixed Sn‐pb Pscsmentioning
confidence: 91%
“…Lastly, the band energy level alignments at the perovskite/ETL and perovskite/HTL interfaces are critical for the performance of PSCs. The ETL and HTL materials commonly used in the Pb‐based PSCs may not be suitable for the mixed Sn‐Pb PSCs . If these issues could be addressed with the use of proper HTL and ETL, the performance of the regular structure mixed Sn‐Pb PSCs is expected to be greatly improved.…”
Section: The Status Of Mixed Sn‐pb Pscsmentioning
confidence: 99%
“…The W F of PEDOT:PSS mixed with PFI increased from 4.71 to 5.41 eV, which leads to the subtle increase in V OC from 0.59 to 0.62 V for P3HT:PC 61 BM based OSCs. [255] For PerSCs, PFI-PEDOT:PSS displayed improved V OC of 0.05-0.15 V. [256,257] However, it should be noted that the increased work function does not necessarily improve the V OC . Interaction between HTL and active layer is important for charge collection.…”
Section: Modification Of Pedot Htlmentioning
confidence: 99%